Case Report: A potentially pathogenic new variant of the REN gene found in a family experiencing autosomal dominant tubulointerstitial kidney disease - Ma, Jingyu; Hu, Zhijuan; Liu, Qiong; Li, Jing; Li, Jiejie (Frontiers in Pediatrics, 2024)
Background: Autosomal dominant tubulointerstitial kidney disease (ADTKD) caused by REN-causing pathogenic variants (ADTKD-REN) is a rare group of heritable diseases. ADTKD-REN often manifests in childhood with symptoms such as mild hypotension, CKD, hyperkalemia, anemia, and acidosis. The diagnosis of ADTKD-REN remains challenging. Case presentation: We describe a 14-year-old boy with acute kidney injury who was found to have a heterozygous missense mutant c.1085G>A;p.Cys362Tyr (not previously reported in the literature)through Sanger sequencing genetic testing. This confirmed a genetic disorder with a probable autosomal dominant inheritance pattern. Notably, despite a family history of autosomal dominant polycystic kidney disease (ADPKD), he was diagnosed with ADTKD. Conclusion：This case identified a new variant in the REN gene, expanding the known spectrum of REN pathogenic variants. Additionally, the importance of family history and genetic testing in confirming the diagnosis is emphasized. Genetic sequencing should be pursued when there are indications for testing.